2010
DOI: 10.1111/j.1475-4762.2010.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there more to environmental participation than meets the eye? Understanding agency, empowerment and disempowerment among black and minority ethnic communities

Abstract: We centred the research gaze on the cultural and ethnic interpretations of environmental dis/ engagement among black and minority ethnic groups, which has been under-explored in the UK literature on public participation. We conducted focus groups with black and minority ethnic communities and in-depth interviews with community representatives and key actors facilitating sustainability policy. We identified from our analysis the sub-themes of a 'different mindset' and 'self-empowering spaces' that demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Importantly, environmental stories figured less prominently than those focused on immigration. Therefore, while immigrant media may theoretically be of significance in communicating climate change information to ethnic groups (Clarke & Agyeman, ), this study echoes the findings of other examinations of Spanish‐language media showing that climate change news and information remain largely invisible to Spanish‐language audiences in the United States (Takahashi et al., ; Villar & Pinto, ). Such silence has important implications for citizenship in terms of justice, social movements, political agency and participation, and may not reflect actual public concern over environmental issues, but rather bottom line decisions by editors and publishers to maximize advertising revenue (Swafford, ; Takahashi, et al., ).…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, environmental stories figured less prominently than those focused on immigration. Therefore, while immigrant media may theoretically be of significance in communicating climate change information to ethnic groups (Clarke & Agyeman, ), this study echoes the findings of other examinations of Spanish‐language media showing that climate change news and information remain largely invisible to Spanish‐language audiences in the United States (Takahashi et al., ; Villar & Pinto, ). Such silence has important implications for citizenship in terms of justice, social movements, political agency and participation, and may not reflect actual public concern over environmental issues, but rather bottom line decisions by editors and publishers to maximize advertising revenue (Swafford, ; Takahashi, et al., ).…”
Section: Discussionsupporting
confidence: 82%
“…While relatively easy and cheap to implement, youth programs like those of Milwaukee’s Urban Ecology Center [70] may have a much larger impact over the access to education, environmental safety, and the environmental quality of Milwaukee’s natural areas when combined with procedural changes that engage youth (and the community overall) in the process of setting environmental clean-up priorities [71,72,73,74]. …”
Section: Resultsmentioning
confidence: 99%
“…Similar work in Minnesota has shown that language barriers, limited access to culturally relevant water recreation, and cultural differences in water recreation are barriers to engaging some communities of color in water management (e.g., MWMO and City of Minneapolis ; Davenport et al ). Research has shown high levels of engagement in social issues such as housing, employment, health, and immigration among CMCs (e.g., Mohai and Bryant ; Clarke and Agyeman ) and lower levels of engagement in environmental issues. This trend was echoed in narratives captured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of environmental participation among communities of color in the United Kingdom found that the formality of facilitated, local sustainability meetings was a constraint to public involvement. This same study found that people of color were more involved in community‐oriented events, rather than environment‐oriented events (Clarke and Agyeman ). Another study focused on the engagement of Hispanic communities found that formal approaches to public participation were not accessible to the broader Hispanic community (Gibson‐Wood and Wakefield ).…”
mentioning
confidence: 89%